Exploring English Lecturers’ Perceptions of Content-Based Instruction in Islamic Higher Education: A Qualitative Case Study in Indonesia - Zulkifli Surahmat; Muhammad Basri; Abdul Halim (AL-ISHLAH: Jurnal Pendidikan, 2025)
Content-Based Instruction (CBI) is widely recognized for enhancing student engagement and integrating language learning with meaningful content. However, its implementation in Islamic Higher Education remains underexplored, particularly regarding English lecturers’ perceptions and practices.This qualitative case study investigates how English lecturers in Islamic Higher Education institutions in South Sulawesi, Indonesia, perceive and implement CBI. Eleven lecturers were selected using purposive sampling. Data were collected through questionnaires, focus group discussions, and classroom observations, then analyzed thematically using ATLAS.ti 24.Findings show that lecturers generally possess a strong understanding of CBI and endorse its application, especially for its ability to enhance student motivation and learning depth. Many reported success in designing interactive, content-rich lessons aligned with students’ academic fields. However, challenges were noted in the balanced integration of language skills—particularly listening, speaking, reading, and writing—which were often fragmented. In addition, some lecturers struggled with adapting instructional materials to meet both content and language objectives effectively.The study highlights both the promise and the limitations of CBI in faith-based contexts. While CBI can support language development and contextual learning, its success relies heavily on lecturers' pedagogical competence, institutional support, and ongoing professional development. Structured training is essential to enhance consistency in language integration and content relevance.